2021
DOI: 10.7717/peerj.12146
|View full text |Cite
|
Sign up to set email alerts
|

DNMT family induces down-regulation of NDRG1 via DNA methylation and clinicopathological significance in gastric cancer

Abstract: Background Aberrant DNA methylation of tumor suppressor genes is a common event in the development and progression of gastric cancer (GC). Our previous study showed NDRG1, which could suppress cell invasion and migration, was frequently down-regulated by DNA methylation of its promoter in GC. Purpose and Methods To analyze the relationship between the expression and DNA methylation of NDRG1 and DNA methyltransferase (DNMT) family. We performed a comprehensive comparison analysis using 407 patients including … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…According to studies by Chang et al., DNMT family DNA methylation may be the cause of the downregulation of NDRG1 expression in gastric cancer. Patients with stomach cancer may benefit from using a demethylating agent as a targeted medication ( 32 ). NDRG1 has significant scientific implications in both prostate cancer and glioblastoma ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to studies by Chang et al., DNMT family DNA methylation may be the cause of the downregulation of NDRG1 expression in gastric cancer. Patients with stomach cancer may benefit from using a demethylating agent as a targeted medication ( 32 ). NDRG1 has significant scientific implications in both prostate cancer and glioblastoma ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…NDRG1 is a member of the NDRG family, which was involved in a variety of physiological functions such as cell differentiation [ 13 ], stress response [ 14 ], and apoptosis [ 15 ]. The RNA-seq data of gastric cancer from the TCGA database demonstrated that the mRNA expression of NDRG1 was downregulated in STAD tumor tissues and was significantly negatively correlated with invasion depth [ 16 ]. NDRG1 overexpression could significantly suppress the proliferation and invasion and could induce a G1 cell cycle arrest in AGS cells [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the m5Cdependent mutual regulation between the nuclear reader ALYREF and the m5C writer NSUN2, leading to the progression of bladder urothelial carcinoma by activating oncogenic RNA through promoting splicing and maintaining stability. DNMT3B (DNA methyltransferase 3B) is a DNA methyltransferase, which is a key enzyme in DNA methylation that can stimulate tumor cell proliferation, migration, and invasion by regulating the promoter of the regulator gene (Caputi et al, 2021;Chang et al, 2021). Research in bladder urothelial carcinoma showed that the DNMT3B-mediated methylation of the transfer inhibitory factor 1 (MTSS1) promoter can suppress its transcription at the epigenetic level (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%